HUBUNGAN TINGKAT PENDAPATAN KELUARGA, PENDIDIKAN DAN PENGETAHUAN DENGAN STATUS GIZI PADA BALITA DI DESA PARIT BARU KABUPATEN KUBU RAYA KALIMANTAN BARAT TAHUN 2014 DESA PARIT BARU KABUPATEN KUBU RAYA KALIMANTAN BARAT TAHUN 2014 - ., Andi Risma Marelda (ProNers, 2014)
Background : The Age of children has very rapid body growth but often alsosuffer from malnutrition. Factors that affect nutrition in children include familyincome, mother's education and knowledge. Data Health Center Sungai Raya inKubu Raya District (2013) the prevalence of nutritional status in the village ofParit Baru in December 2013 totaled 507 toddlers with malnutrition statuspercentage of 3.7%, 95% good nutritional status and nutritional status of over0.8%.Purpose : This study aims to determine the relationship of family Income level,education and knowledge of the nutritional status of children under five in KubuRaya District of Parit Baru villageMethodology : Research conducted analytical research design with crosssectional approach. The population around the mother who has a toddler (1-5years) in Kubu Raya District of Parit Baru village totaling 2216 respondents.Sample used by 92 respondents with sampling techniques of porposive sampling.Data was analyzed using univariate and bivariate. Hypotheses statistical analysisused the Kolmogorov-Smirnov analysis test.Result : The result of the salary household categorized a low income that obtainedmost 48 respondents (52.2%). The results of the study that majority ofrespondents are basic (elementary and junior high school) were have 62respondents (67.4%). The results of the study of maternal knowledge level of themajority have a good knowledge of as many as 78 respondents (84.8%).  Conclusion : Results of statistical analysis showed no significant relationshipbetween Income level of families with children under five nutritional status (p =0.299), there was no significant relationship between mother education andnutritional status toddlers (p = 0.218) and there was no significant relationship  between mother knowledge the nutritional status toddlers (p = 0.473).Keywords:  Income level, education, knowledge, nutrition status.References:  28( 2001-2013)